The Existence of Sharia Courts in the United Kingdom - Maria Ulfah Syarif; Susmihara Susmihara; Syamsudduha SyamsudduhA; Mardhati Mardhati (Al-Adalah: Jurnal Hukum dan Politik Islam, 2023)
The Islamic Risala brought by Muhammad SAW has been presented as the last heavenly religious teaching that carries a mission of peace with the Qur'an as the guidebook of his people. The study of all life aspects contained in the Qur'an is Hudan (guidance), and it is the most complete guide for all humans in the world. The authenticity of the Qur'an and language style has been unrivaled throughout the ages, and it strengthens the perfection of Islamic teachings, which is universal as Rahmatan Lil' ālamīn. As time goes by, Islam has significantly contributed to the history of human civilization. History also records areas where great civilizations have emerged. There are relics of high Islamic culture, admired and recognized, including in the European region, definitely cannot be separated from the contribution of the struggle of Muslim leaders who are highly dedicated and persistent in spreading Islamic teachings. As a European country, the United Kingdom was not spared from the spread of Islamic teachings. By collecting research data from various works of literature and making the world of texts the main object of its analysis, this article intends to examine the track record of the early embryo of the universality of Islam touching British society by looking deeper into the history of the beginning of the arrival of Islam, the Dynamics of Muslim life and Sharia Courts in the United Kingdom.